Alterations in Tumor DNA Are Related to Short Postoperative Survival in Patients Resected for Pancreatic Carcinoma Aimed at Cure. Issue 6 (July 2016) - Asting, Annika Gustafsson; Ljungman, David; Carén, Helena; Dambrauskas, Zilvinas; Iresjö, Britt-Marie; Hyltander, Anders; Naredi, Peter; Lundholm, Kent
Abstract : Objectives: Pancreatic ductal adenocarcinomas (PDACs) are found in more than 85% of patients with pancreatic cancer and with 5-year survival of less than 10%. Effective treatment may be radical surgery, which is hampered by rapid relapse. Therefore, our aim was to compare DNA sequence alterations in patients with short and long survival to evaluate if confirmed DNA alterations predict short postoperative survival. Methods: DNA was extracted from tumor tissue from 59 PDAC patients, analyzed for KRAS mutations, and hybridized to 180 K CGH + SNP microarrays and 450 K methylation arrays. Analyses were based on postoperative survival where less than 12 months was considered to be short survival and more than 18 months was considered long survival. Results: Ninety-three percent of the patients had KRAS mutations in tumor DNA. Great heterogeneity of whole genome DNA sequence alterations were observed among chromosomes within the patient materials. Specific DNA sequence alterations did not directly predict postoperative survival, although short survivors had significantly more and larger DNA amplifications ( P < 0.006). Amplifications on chromosome 11 and 21 and deletions on chromosome 2 predicted short postoperative survival ( P < 0.03). DNA methylation was not related to survival. Conclusions: Highly variable genetic differences among DNA regions in PDAC tumors were demonstrated. Postoperative short survival was related to tumor sequence DNA alterations on chromosome 2, 11, and 21.